THE EFFECT AROMATHERAPY CAJUPUT OIL CONCERNING EMESIS GRAVIDARUM ON PREGNANT WOMEN TRIMESTER 1 IN INDEPENDENT MIDWIFE'S CLINIC NY F PONOROGO - Rindang Fitriana Ulfa; Sri Haryuni; Ediatmi Ediatmi (Akbid Harapan Mulya Ponorogo, 2018)
Emesis Gravidarum can be very disturbing activity and impact on the maternal and fetal maternal obstacles. The incidence of emesis gravidarum in the world is 70-80% of the number of pregnant women, one non-pharmacological method that can reduce the intensity of nausea vomiting by cajuput oil. The purpose of this study was to determine whether there is an influence of aromatherapy cajuput oil on emesis gravidarum in pregnant women trimester 1 in clinic Ny F Ponorogo City Year 2015 This research is survey research with cross sectional approach. Population in this research is trimester 1 pregnant woman at clinic Ny F city of Ponorogo year 2015 which amounted to 17 pregnant women taken by using total sampling. The data were analyzed by univariate analysis with independent variable frequency distribution and dependent and bivariate analysis using Wilcoxon sign rank test. P-value value: 0.000 and alpha 0.005 Statistical test results show that cajuput oil has a significant effect on emesis gravidarum intensity. It can be concluded that there is an effect of Aromatherapy cajuput oil on emesisgravidarum in trimester 1 pregnant woman, so it is expected that cajuput oil can be one of alternative non pharmacological method that can help to reduce the intensity of emesis gravidarum